A metabolomic study of fipronil for the anxiety-like behavior in zebrafish larvae at environmentally relevant levels. (April 2016) - Wang, Cui; Qian, Yi; Zhang, Xiaofeng; Chen, Fang; Zhang, Quan; Li, Zhuoyu; Zhao, Meirong
Abstract: Field residue of fipronil can interfere with the physiological characters of the domesticated fish; thus, lethal dose test and the general biomarker cannot delineate the low-level situation. Manipulating by video track, we observed an anxiety-like behavior including high speed and abnormal photoperiod accommodation after exposure to fipronil at environmental typical dose in zebrafish larvae. Examining the unbiased metabolomic profiles, we found perturbation in several metabolic pathways, including the increased contents of fatty acids and glycerol and the decreased levels of the glycine, serine, and branched amino acid. We presumed that observed enhanced fatty acid utility was in response to increase energy demands caused by anxiety like behavior. Additionally, the body burden of neurotransmitter such as glycine andl -glutamate may concurrently stimulate the swimming behavior. The insight of this study showed that integral perturbation such as metabolism helps us to further understand the risk to aquatic fish at the environmentally relevant levels. Highlights: Fipronil increased the swimming speed at 10 μg/L to zebrafish larvae. Accommodation to light–dark photoperiod switch was disturbed by fipronil. Metabolomics indicated an increase energy availability for anxiety-like behavior. Anxiety-like behavior induced by fipronil may attribute to neurotransmitter changes. Abstract : Zebrafish larvae exposed to environmentally relevant concentrations of fipronil display anxiety like behavior that may attribute to observed changes in energy utilization and neurotransmitter disturbances.